Investigations on the role of insulin and scorpion antivenom in scorpion envenoming syndrome - K. Radha Krishna Murthy; Dubey As; M. Zare Abbas; L. Haghnazari (Journal of Venomous Animals and Toxins including Tropical Diseases, 2003)
Acute myocardiopathy in alloxan treated experimental dogs and rabbits was induced by subcutaneous (SQ) injection of scorpion venom from Mesobuthus tamulus concanesis, Pocock. Envenoming resulted in an initial transient hypertension (180-320 mm Hg.) followed by hypotension. Simultaneous administration of venom and species-specific scorpion antivenom (SAV) prevented hypertension and hypotension. Hypotension did not occur when SAV was given 60 min after envenoming. Blood glucose, triglycerides, cholesterol, amylase, insulin, glucagon, cortisol, hematocrit, mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), platelet count, red blood cell (RBC) count, hemoglobin (Hb), 2,3-diphosphoglycerate (2,3-DPG), and glutathione levels were increased 60 and 90 min after envenoming. Total white blood cell (WBC) count was reduced 60 min and increased 90 min after envenoming. Simultaneous administration of venom and SAV did not alter Hb, MCHC, and packed cell volume (PCV) levels, or ECG, and cardiovascular, biochemical, metabolic, and hormonal changes. Hematological parameters were reversed when SAV was given 30 and 60 min after envenoming. PCV, Hb, and MCHC values returned to normal 120 min after SAV. Alloxan-treated dogs showed increased blood glucose, cholesterol, glucagon, cortisol levels; reduced glycogen content of liver, cardiac and skeletal muscles; and reduced insulin levels and insulin/ glucagon ratio (I/G ratio). Envenoming in the alloxan pre-treated dogs further increased these levels and reduced tissue glycogen content, insulin levels, and I/G ratio. Administration of 4 U of insulin to alloxan pre-treated envenomed rabbits caused a biochemical and clinical improvement and increased glycogen content of all tissues in comparison with the values from those administered with SAV to alloxan pre-treated envenomed animals. SAV administration to envenomed alloxan pre-treated rabbits did not cause clinical or biochemical improvement. Severe scorpion envenoming causes an autonomic storm with a massive release of catecholamines and other counter-regulatory hormones; changes in insulin secretion resulting in fuel energy deficits producing multi-system-organ-failure (MSOF); and death. Administration of either insulin or SAV (through the release of insulin) appears to be the physiological basis for the control of the metabolic support to control the adverse effects triggered by counter-regulatory hormones.